(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2014)
Two new species of Pentagonia (Rubiaceae) from the Department of Chocó in western Colombia are here illustrated and described: P. chocoensis, a treelet that occur in the Río Fujiadó area, a tributary of Río San Juan. This new species is characterized by having a combination of entire leaves with long petioles and mainly by having calyces with highly distinctive narrowly-lanceolate to caudate lobes, 15–22 × ca. 3 mm. The second new species is P. imparipinnata, a shrub collected along the road Sapzurro-La Maloka, at the Municipio Acandí. The latter taxonomical novelty is characterized by having compound imparipinnate leaves and inflorescences with thick peduncles bearing developed basal bracts that are similar in shape to that of the stipules. The compound imparipinnate leaves of P. imparipinnata are a strikingly new characteristic for the genus and the Rubiaceae family.